Exploring Acute Kidney Injury Incidence in Hip Periprosthetic Joint Infection Treatment With Combined Intravenous and Intra-articular Antibiotic Infusion - Wenbo Mu, MD, PhD; Boyong Xu, MD; Fei Wang, MD; Wentao Guo, MD, PhD; Xiaogang Zhang, MD; Li Cao, MD (Arthroplasty Today)
Background: Periprosthetic joint infections (PJIs) are a significant complication following total hip arthroplasty, impacting patient health and healthcare costs. This study examines the incidence of acute kidney injury (AKI) in patients undergoing hip PJI treatment with a combination of intravenous and intra-articular antibiotic infusion therapies. Methods: A retrospective review of 151 patient records from May 1, 2010 to December 30, 2022 was conducted at a single academic hospital. Patients were treated for hip PJIs using debridement, antibiotics, and implant retention or single-stage revision surgeries. AKI was classified according to the Kidney Disease: Improving Global Outcomes criteria. Results: Among 151 patients, 17 (11.26%) developed AKI, with 13 cases resolving transiently before discharge. The median onset of AKI was on postoperative day 2, with stage I AKI being the most prevalent, accounting for 64.71% of cases. Diabetes and low baseline serum creatinine levels were identified as independent risk factors for AKI, with odds ratios of 9.69 and 1.09, respectively. Conclusions: The combined regimen of intra-articular and intravenous antibiotic infusion appears to have a manageable risk profile regarding AKI. This approach could serve as a viable alternative for PJI management, emphasizing the importance of careful patient monitoring and tailored antibiotic regimens. Further studies are recommended to optimize treatment protocols and mitigate risks.